At the vanguard: Leaders' perspectives on establishing healthcare system infection prevention programs - Michael P. Stevens; Sharon B. Wright; Keith S. Kaye; Jerry M. Zuckerman; Catherine L. Passaretti; Richard A. Martinello; Hilary M. Babcock; Michael B. Edmond; Graham M. Snyder (Cambridge University Press, 2022)
Hospitals are increasingly consolidating into health systems. Some systems have appointed healthcare epidemiologists to lead system-level infection prevention programs. Ideal program infrastructure and support resources have not been described. We informally surveyed 7 healthcare epidemiologists with recent experience building and leading system-level infection prevention programs. Key facilitators and barriers for program structure and implementation are described.